How Jawi Script Influences Religious Attitudes: An Evidence from Aceh - Zulkhairi, Teuku; Hajar, Ibnu (Jurnal Ilmiah Peuradeun, 2023)
This study described the religious attitudes influenced by the Jawi Script upon people living in the Seulimeum Subdistrict of Aceh Besar District, Indonesia. The data for this qualitative study were gathered through interviews and observations that included three activities: behavioral observation, direct questioning, and direct disclosure. A checklist and field notes accompanied observations, while direct questioning and direct disclosure involved unstructured interviews with eight respondents. The data was then qualitatively analyzed using descriptive analysis techniques. The study's findings suggested that the Jawi script instructional process had influenced respondents’ religious attitudes toward aqidah, ibadah, morals, and social society. In the field of aqidah, Jawi script instructional process strengthened the aqidah that adheres to the creed of Ahlusunnah wal Jama’ah. They also rejected another aqidah, armed with knowledge from the Jawi Script. Religious attitudes also were reflected in ibadah activities under the knowledge learned from the Shafi'i school of thought's Jawi Script. Regarding morals and social society, Jawi script instructional process strengthened husband-wife relationships, strengthened social traditions with Islamic nuances, and fostered social unity.